ESG, Stock Returns, and Sustainable Investment: A Systematic Literature Review - Zanu’ddin, Mohammad; Djaddang, Syahril (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study aims to synthesize empirical evidence regarding the influence of Environmental, Social, and Governance (ESG) factors on stock returns using a Systematic Literature Review (SLR) approach. The analysis results indicate that the implementation of ESG generally has a positive effect on stock returns, primarily through mechanisms such as reducing extreme risks, enhancing corporate reputation, and improving governance efficiency. Nevertheless, this relationship is not universal, different outcomes are observed between developed and emerging markets depending on the economic context, regulatory environment, and investor perception. ESG has been proven to play an important role in building market trust and sustaining corporate value. The findings of this study reinforce the view that ESG is not merely a tool of business ethics but a long term investment strategy aimed at creating sustainable economic value.